The novel and the ideology The story of the last Arab by Wassini Al-Araj as a model - boudiaf, ahmedamine (The Notebooks of the Algerian Poetics Laboratory Journal, 2022)
In our research paper، we dealt with the novel “The Story of the Last Arab 2084” by the Algerian novelist “Wasini Al-Araj” with its contents of ideology and political struggle. And how did the typical components of the novel manifest in times، places، events، characters and narrative language?